Finding the skeleton key to happiness: evaluating model invariance of subjective well-being in a comparison of large urban centres worldwide. (28th October 2019) - Cramer, Kenneth M.; Pschibul, Rebecca
How well we can we predict a citizen's happiness? Numerous antecedent factors - including higher creativity, optimism, longevity; and lower hostility and self-centredness - have been identified as important. The present study compared the antecedents that contribute to personal happiness from several large urban centres around the world, testing the hypothesis of model invariance that supposes any given model may be applied globally. Data from an archival dataset (Lee, 2006) included various elements of city life: economy, culture and education, income, safety, living conditions, city administration, health, city pride, and current level of happiness. Results showed each urban centre required a unique profile of antecedents, offering little evidence to support the invariance assumption. Overall, health was the most common predictor of happiness (especially for males), followed by city pride and household income. Lower explained variance was typical among the samples, suggesting that additional factors are required to capture the scope of urban quality of life. Future research directions are discussed.